Distribution of Lymphoma Subtypes in Bihar—Analysis of 518 Cases Using the WHO Classification of Lymphoid Tumors (2017) - Lisa, Mona; Verma, Pranab Kumar; Shuchismita; Nishi; Mustaqueem, Syed Fiza (Journal of Laboratory Physicians, 2020)
Introduction The prevalent spectrum of the major subtypes of lymphoma varies across geographical regions. Through this study we aim to study the distribution of lymphoma in the state of Bihar by studying the immunophenotypic features and classifying them according to World Health Organization (WHO) 2017. To the best of our knowledge, this is the first study of this type from BiharPatients and Methods All the cases diagnosed as lymphoma between January 2016 and June 2019 in the Department of Pathology Mahavir Cancer Sansthan were included in the study. The cases were reviewed by two pathologists and diagnostically difficult cases were referred to higher center for opinion. A total of 518 cases were diagnosed as lymphoma.Results B cell lymphomas formed 79.1%, whereas T cell lymphomas formed 16.2% of the total. Hodgkin lymphoma (HL) was seen in 19.6% cases. Among the non-Hodgkin lymphoma (NHL), diffuse large B cell lymphoma was the most common subtype (58% of all NHLs). Follicular center-cell lymphomas, B cell small lymphocytic lymphoma, mantle-cell lymphoma, and marginal zone B cell lymphomas (including mucosa-associated lymphoid tissue lymphomas) amounted to 2.1, 6.9, 4.5, and 0.95%, respectively. Among the T cell lymphomas, T cell lymphoblastic lymphoma, anaplastic large-cell lymphomas of T/null-cell type, and other nodal peripheral T cell lymphomas accounted for 4.7, 8.1 and 6.6% of all cases, respectively.Conclusions The prevalence of lymphoma subtypes in India is different from the rest of the world. We have analyzed the distribution of lymphomas in Bihar and compared it with other studies from India. Follicular lymphoma and mantle-cell lymphoma are less common in India compared with the west. Peripheral T cell lymphomas and T/NK-cell lymphomas of nasal types are less prevalent than some Asian countries but are more prevalent than the west. T cell lymphoblastic lymphoma and anaplastic large T/null cell lymphoma are more common in India.
Keywords: epidemiology; lymphoma; WHO 2017